2021
DOI: 10.1183/13993003.01454-2021
|View full text |Cite
|
Sign up to set email alerts
|

Right atrial function is associated with right venticular diastolic stiffness: RA–RV interaction in pulmonary arterial hypertension

Abstract: BackgroundPulmonary arterial hypertension (PAH) patients have altered right atrial (RA) function and right ventricular (RV) diastolic stiffness. This study assessed the impact of RV diastolic stiffness on RA-RV interaction.MethodsLow or high end-diastolic elastance (Eed) PAH patients (n=94) were compared to controls (n=31). Treatment response was evaluated in n=62 patients. RV and RA longitudinal strain, RA emptying and RV filling were determined and diastole was divided in a passive and active phase. Vena cav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 25 publications
(42 reference statements)
0
15
0
Order By: Relevance
“…46 Poor RV diastolic function resulted in lower RV passive filling and improvements in RV diastolic function with treatment were associated with improved RV active filling and stroke volume. 47 These findings suggest that RA dysfunction assessed by STE may be a sensitive marker of right-sided overload preceding echocardiographic manifestations of RV failure, with important prognostic implications.…”
Section: Speckle-tracking Echocardiographymentioning
confidence: 82%
“…46 Poor RV diastolic function resulted in lower RV passive filling and improvements in RV diastolic function with treatment were associated with improved RV active filling and stroke volume. 47 These findings suggest that RA dysfunction assessed by STE may be a sensitive marker of right-sided overload preceding echocardiographic manifestations of RV failure, with important prognostic implications.…”
Section: Speckle-tracking Echocardiographymentioning
confidence: 82%
“… 100 Thus, non‐invasive measurement of RA parameters for PH risk stratification 34 somewhat embodies assessment of RV diastolic function, as suggested by the authors. 100 However, RA impairment and RA pressure increase may not always be the consequence of RV dysfunction per se and must be evaluated in the context of the underlying disease, as recently shown by van Wezenbeek et al ., comparing PAH and PH in HFpEF at matched levels of pressure overload. 101 Consequently, simple non‐invasive surrogates of RV diastolic function are sought and may attract attention in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Wessels et al . recently demonstrated that RV diastolic impairment alters right atrial (RA) function in PAH 100 . Thus, non‐invasive measurement of RA parameters for PH risk stratification 34 somewhat embodies assessment of RV diastolic function, as suggested by the authors 100 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to elevation of RAP (29). Namely, RAP is a surrogate marker of both right ventricular diastolic function and right ventricular diastolic stiffness (30)(31)(32)(33). Furthermore, these series of processes lead to reduction of venous return to the right ventricle, and result in loss of right ventricular stroke volume and right ventricular dysfunction.…”
Section: Discussionmentioning
confidence: 99%